Dasar Pertimbangan Hakim Atas Gugurnya Permohonan Praperadilan ( Studi Putusan Praperadilan Nomor : 02/Pid.Pra/2023/Pn.Pnn) - Frischa Kurnia Dwi Septilawati; Engrina Fauzi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The pre-trial application is an attempt to resolve criminal cases in Indonesia and deserves special attention.Law enforcement efforts are part of an effort to create order, security, and peace in society.Law enforcement measures must be implemented responsibly, in accordance with the rules of the laws in force. (prosedur hukum).The pre-judicial stage is regulated in the Covenant which contains provisions on when the pre-trial stage is declared invalid.The pre-trial review ended at the time the re-examination of the case had begun by the State Court, while the pre-judicial review had not yet ended.The provisions concerning the time of derogation of pre-trial jurisdiction on the basis of the provisions of the Covenant are applied by the judge in various pre-judicial examinations, with the preference of the interpretation of each judge. Based on the description above, then the problem that the author discusses in this book is (1).How to regulate unprocessed deaths from the point of view of criminal law (2).On what basis the judge considers to reject the pre-trial application. This study uses a normative jurisprudential approach. The sign that the author submits is that the pre-judicial death arrangement is included in the establishment of pre-trial institutions in the Act No. 8 of 1981 on HAPPENING. (selanjutnya disebut KUHAP). As stated in Section 1, Section 10.Bab X, Sections 77 to 83, Section 1 The basis of the judicial consideration of the invalidity of the pre-trial application in the practice of criminal prosecution is the existence of different interpretations, but the first interpretation is a pre-judicial application failed since the file of the case was submitted to the state court by the prosecutor. The second interpretation states that the preliminary hearing ends from the beginning of the first hearing of the matter. The author suggests that the judge be more careful and careful in deciding whether to reject a pre-trial application. To ensure that the complainant (who is suspected of being a suspect) does not feel that his human rights have been violated,